Clinic and Diagnosis of Iron Deficiency in Adolescent Students (Eurasian Medical Research Periodical, 2022)
Anemia is a very common pediatric problem. WHO data show that more than 47% of preschool children and more than 25% of school-age children suffer from anemia. Anemia in children develops for a variety of reasons, and predisposes to this rapid growth of the body. In children, erythropoiesis (the formation of red blood cells) is accelerated, the number of cells and the volume of circulating blood must constantly increase in order to keep up with growth. This process is often disrupted due to agerelated immaturity of hematopoiesis.